Exploring Young Children's Social-Emotional Adjustment: Insights From Peer Interaction Patterns - KILIÇ, SELİN; AYDIN, EBRU (Routledge Journals, Taylor & Francis Ltd, 2025)
This study explored young children's social-emotional adjustment within peer interactions using an explanatory sequential design. Quantitative data were collected from 258 five-year-old children to assess their social-emotional adjustment levels. Subsequently, observational data were gathered on ten children - representing the highest and lowest adjustment levels - during peer interactions in a natural classroom setting. Children with high adjustment frequently provided emotional and motivational support, invited peers to play, led games, and showed affection, though they occasionally exhibited complaints and verbal aggression toward peers. Conversely, children with low adjustment levels tended to avoid interaction, experience peer rejection, engage in onlooker or solitary play, and display behaviors such as taking items without permission, behavioral and verbal aggression, and reluctance to share. Notably, both high - and low-adjustment groups displayed some shared behaviors, including game leadership, peer complaints, and verbal aggression. These findings underscore the complex behavioral patterns characterizing children's social-emotional adjustment in peer interactions.
Keywords: Social-emotionalad Justment; Early Childhood; Peer Interactions; Mixed-methods Research; Classroom Observation